Perceptions of large language models in medical education and clinical practice among pediatric emergency physicians in Saudi Arabia: a multiregional cross-sectional study - Yara AlGoraini; Mashhour Alsayyali; Ola Alotaibi; Ibtihal Almeshawi; Fahad Alaifan; Rawan Alrashed (Frontiers in Public Health)
BackgroundArtificial intelligence (AI) is reshaping healthcare delivery and education, but little is known about its perceived value among pediatric emergency medicine (PEM) physicians in Saudi Arabia. This study aimed to assess the perceptions and experiences of PEM physicians in Saudi Arabia toward the use of AI, particularly ChatGPT, in clinical practice and medical education.MethodsA cross-sectional, web-based survey was conducted among 100 PEM physicians across various regions of Saudi Arabia. The questionnaire explored demographics, AI experience, perceived benefits and limitations, and the evaluation of ChatGPT-generated clinical and educational content.ResultsMost participants (96%) believed that AI tools, such as ChatGPT, would play a significant role in the future of PEM. A high agreement was observed regarding AI’s usefulness in medical education (91%) and clinical practice, particularly in differential diagnosis (77%) and documentation (78%). The ChatGPT-generated responses to a clinical scenario (croup) were rated highly for validity, reasoning, and educational value. However, 66% of them still preferred traditional textbooks for complex topics. The key concerns included accuracy (83%), patient safety (56%), and lack of regulatory guidance (52%).ConclusionSaudi PEM physicians show a strong interest in integrating AI tools, such as ChatGPT, into clinical and educational workflows. Although optimism is high, concerns about safety, ethics, and oversight highlight the need for regulatory frameworks and structured implementation strategies.